Do trade unions cause inflation? : two studies: with a theoretical introduction and policy conclusion - Jackson, Dudley; Turner, H. A.; Wilkinson, Frank (Cambridge [Eng.] : University Press, 1972)
The book discusses inflation, strato-inflation and social conflict; the wage-tax spiral and labour militancy.
Includes bibliographical references.
rua 16/05/17; usc 15/5/18
Loans
Keywords: Inflation (Finance); Wages; Income tax